2012
DOI: 10.1021/jp302026n
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Analysis of the Interactions of GaN Clusters with Oxygen and Water

Abstract: We calculate the interactions of oxygen and water with the Ga-face of GaN clusters, which could be used as testbeds for the actual Ga-face on GaN crystals of importance in electronics; however, our additional goal is the analysis of the nanoclusters for several other applications in nanotechnology. Our results show that the local spin plays an important role in these interactions. It is found that the most stable interaction of O2 and the GaN clusters results in the complete dissociation of the O2 molecule to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We have chosen the GaN(0001) surface/water interface as a model system because GaN has better crystal quality compared to other photocatalysts, which makes easier the comparison between computational and experimental results. It is worth mentioning that GaN electrode has attracted considerable attention for photocatalytic applications. Water adsorption on GaN surface itself is also of interest in the context of surface chemistry; it has been studied extensively by first-principles calculations, and several attempts have been made to determine the surface structure using photoelectron spectroscopy. Recently, Zhang and Ptasinska pointed out the strong correlation between the electronic and chemical properties of the water adsorbed GaN(0001) surface . However, in spite of substantial effort, an atomistic model for the physisorbed and chemisorbed water layers has not yet been defined …”
Section: Introductionmentioning
confidence: 99%
“…We have chosen the GaN(0001) surface/water interface as a model system because GaN has better crystal quality compared to other photocatalysts, which makes easier the comparison between computational and experimental results. It is worth mentioning that GaN electrode has attracted considerable attention for photocatalytic applications. Water adsorption on GaN surface itself is also of interest in the context of surface chemistry; it has been studied extensively by first-principles calculations, and several attempts have been made to determine the surface structure using photoelectron spectroscopy. Recently, Zhang and Ptasinska pointed out the strong correlation between the electronic and chemical properties of the water adsorbed GaN(0001) surface . However, in spite of substantial effort, an atomistic model for the physisorbed and chemisorbed water layers has not yet been defined …”
Section: Introductionmentioning
confidence: 99%
“…A second group of materials that exhibits a similar kind of low-temperature response, is III-nitride materials both in the form of AlGaN/GaN high electron mobility transistors (HEMT) with flat surface morphologies [ 14 , 15 , 16 , 17 , 18 , 19 ] as well as in the form of GaN/InGaN nanowire heterostructures [ 20 , 21 , 22 ]. These effects can be attributed to the fact that III-nitride surfaces tend to develop surface oxides when exposed to ambient air which makes them similar to conventional MOx materials [ 23 , 24 , 25 , 26 , 27 , 28 ]. A third group of materials that exhibits a well-documented low low-temperature gas response is hydrogenated diamond.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a microscopic picture of the intrinsic mechanism and hence predict suitable photocatalysts, many theoretical calculations estimated the band gaps and band edge positions of known and potential materials. , Some of these works even analyzed band structures and/or predicted the light absorption spectra. Many other theoretical works studied the water/photocatalyst interface structure and/or thermal dynamics of water molecules and adsorbates to understand the water splitting processes from an atomic point of view. , In one of our previous works, we observed that it is much easier to produce oxygen gas molecules than H 2 on (101̅0) nonpolar surface, while the polar surface behaves in a reverse way. The paths for removing other water adsorbates (hydroxyl groups, hydrogen, and oxygen adatoms) from GaN surfaces are still undetermined.…”
Section: Introductionmentioning
confidence: 99%